PARTICIPATIVE LEARNING TO IMPROVE FEMALE ADOLESCENTS’ KNOWLEDGE ON THE RISKS OF EARLY-AGE MARRIAGE - Merry Wijaya; Fardila Elba (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Early-age marriage is still one of the most prominent issues in female health in Indonesia. Scarce information on the risks and dangers of early-age marriage has caused many adolescents to make a rash decision to get married. This study aims to discover the effectiveness of participative learning on the risks of early-age marriage in improving female adolescents’ knowledge about the matter. This is a quantitative study in quasi-experimental design, using pretest-posttest design method, conducted at Kalijaya and Kalisari Villages, Karawang Regency, on May 2018. The sample of 80 girls from Kalijaya Village and 101 girls from Kalisari Village was selected through purposive sampling from the population of all female adolescents at those villages. Data is obtained from two sources, questionnaire (for primary data) and annual report register in local Religious Affairs Office (for secondary data). Data is analyzed using paired T-test and effect-size (ES) measurement. The results show that in Kalijaya Village, the pretest score of R=69.10, s.b=16.45 increase to a posttest score of M = 77.58, SD = 15.88, [t(80) = 6.75, p = 0.000], and the pretest score of M = 66.14, SD = 15.38 in Kalisari Village increase to a posttest score of M = 76.36, SD = 16.10 [t(101) = 7.65, p = 0.000]. The intervention of participative learning has high effectiveness (ES ≥ 0.14) in improving female adolescents’ knowledge on the dangers and risks of early-age marriage (ES = 0.37). Health education using participative method is effective to improve female adolescents’ knowledge on the risks of early marriage.